Práticas de cuidados paliativos em Instituição de Longa Permanência para Idosos - Evellyn Aparecida Almeida Rodrigues (2021)
The world has undergone a process of demographic transition, with an increase in the number of elderly people in society. The change in epidemiological settings, combined with social, economic, and family related changes, has led to an escalationin institutionalization rates, reverberating in vacancies in Long-Term Care Facility (LTCF) for older adults demand boost. The reason for admission in a LTCF, for most residents, is the presence of chronic diseases.These facilities often take care of the elderly until their death. Therefore, palliative care practices have been getting closer to these institutions. Due to this new adopted strategy, concerns have been raised regarding palliative services offered to LTCF residents, making it important to understand the institutional practices. This study aimed to identifythe palliative care practices used inside a LTCF institution, from the perspective of a multidisciplinary team. We performed a qualitative approach, which was conducted at a philanthropic LTCF in Belo Horizonte, Brazil. 12 members of the institution’s multidisciplinary team were enrolled in this study. The studied individuals took part in the daily practice of palliative care delivered to the residents. Data was collected through observation and interviews with the participants. Further, it was submitted to content analysis organized into three categories: dimension of palliative care in the LTCF, subjectsinvolved in palliative care practices in the LTCF and organization of palliative care practices management. In the first previously mentioned category the dimensions discussed were: palliative care for the promotion of better quality of life, palliative care as care tool and comfort, palliative care as a care performed in the final phase of life and palliative care and spirituality. The second studied category we selected as subjects the healthcare providers who performed palliative care for the elderly, elderly individuals in palliative care, the elderly’s family, and the interface of the other elderly who resided in the LTCF. Lastly, in the third category, the dimensions analyzed included the palliative care routine, environment organization and palliative care practices, construction process of palliative care and adaptations imposed by the COVID-19 pandemic. Thus, we concluded that the present study enabled the identification of the dimensions of palliative care practices in the LTCF. The palliative care approach has beenshowed to be essential for the caring of institutionalized elderly, as it is focused in quality of life, symptoms reduction and suffering mitigation. In the development of palliative care practices, it is important to include all involved subjects. The multidisciplinary team approach and knowledge proved to be relevant to these practices. Practices that followed the principles of palliative care can befound in the institutional routine. It is important to reinforce the importance of educational actions directed to healthcare providers professional growthwho work at LTCF in regard to palliative care. The limitation of this study is that data collection was carried out in only one institution. The development of further studies in this area could assist in creating more in-depth knowledge on this topic.